Knowledge And Practice of Preconception Care Among Women of Reproductive-Age in Bheerkot Municipality, Nepal - Godar, Mousami; Sharma, Krishna; Raj Adhikari, Keshab (Journal of Women's Reproductive Health, 2023)
Background Preconception care is a crucial aspect of maternal and child healthcare services that aims to mitigate adverse pregnancy outcomes and enhance the desired health outcomes for women, newborns, and children. Despite the continuous multi-sectoral efforts in preconception care, maternal mortality and morbidity remain significant health concerns globally. This study aimed to assess the knowledge and practice of preconception care and its associated factors among women of reproductive age in Bheerkot Municipality, Nepal.  Methodology A community-based descriptive cross-sectional study was conducted among 215 reproductive-age women to assess knowledge and practice regarding preconception care in Bheerkot Municipality, Nepal. Structured questionnaires were designed in the Nepali language and used in face-to-face interviews. We used a simple random sampling technique to collect quantitative data. In a statistical analysis, we employed the Chi-squared test and logistic regression analysis to identify possible predictors using the odds ratio and considered variables with p<0.05 statistically significant at a 95% confidence interval. Result Out of the 215 women who participated in the study, only 46.9% had a good knowledge of preconception care. Approximately half (43.7%) of the respondents had never practiced preconception care. Among respondents who had practiced preconception care before, 47.9% reported good practice, and 52.1% reported poor practice. Age of the respondent (χ2=14.2063, P=0.000823, df=1), marital status (χ2=17.9851, P=0.000022, df=1), time to reach a health facility (χ2=30.1371, P=0.00001, df=1), and age at first pregnancy (χ2=4.7975, P=0.0285, df=1) were statistically associated with knowledge about preconception care. Women who have foreign employment as a major source of family income and whose age is from 25 to 34 years were more likely to have a better practice of preconception care than their counterparts (COR 3.5000, CI 1.3343 to 9.1805, P = 0.0109) and (COR 3.4000, CI 1.1646 to 9.9265, P = 0.0252), respectively. Additionally, out of those who practiced preconception care, most respondents (93.4%) have practiced it in government health facilities. Conclusion Respondents had relatively poor knowledge and practice of preconception care. Collaboration of governmental health institutions between multiple sectors at local levels for more education and information and a specific national protocol or policy formulation would be beneficial in improving preconception care in Nepal.
Keywords: Preconception Care; Pregnancy; Reproductive-age Women; Nepal